Process Mineralogy Characteristics and Flotation Application of a Refractory Collophanite from Guizhou, China - Wei Xu (MDPI AG, 2021)
A refractory phosphate ore obtained from Guizhou, China, contains high amounts of detrimental metal impurities (e.g., Fe, Al, and Mg) which affect the deep wet processing of phosphorus products before use. In this study, mineralogy parameters of the ore such as mineral composition, disseminated particle size, mineral liberation degree, and intergrowth relationship were investigated using X-ray fluorescence spectrometer (XRF), X-ray powder diffractometer (XRD), and advanced mineral identification and characterization system (AMICS). The mechanism for flotation separation was also discussed. The results showed that the ore was a fine-grained calcareous-siliceous collophanite with high P2O5 grade. The gangue minerals such as quartz, sericite (muscovite), pyrite, and dolomite were finely disseminated and encapsulated by fluoroapatite particles in a rather complex relationship. A double reverse flotation process was carried out based on the separation principle of less flotation and more inhibition. A phosphorous concentrate with a P2O5 grade of 35.53%, SiO2 content of 5.88%, MgO content of 0.91%, sesquioxide (Fe2O3 + Al2O3) content of 1.98%, MER value of 8.13%, and phosphorus recovery of 75.04% was obtained. Based on the flotation test results and the analysis of process mineralogy parameters, we concluded that the main causes of difficulty in separation of collophanite are fine disseminated particle size, poor mineral liberation degree, and serious argillization. The selection of foam-controlled collectors, efficient dispersing inhibitors and classified desliming process will be necessary for improving flotation index. These results provide a technical reference for subsequent development and utilization of collophanite resources.